Association of sleep-related disorders with cardiovascular disease among adults in the United States: A cross-sectional study based on national health and nutrition examination survey 2005–2008 - Kadier, Kaisaierjiang; Qin, Lian; Ainiwaer, Aikeliyaer; Rehemuding, Rena; Dilixiati, Diliyaer; Du, Yi-Ying; Maimaiti, Halimulati; Ma, Xiang; Ma, Yi-Tong (Frontiers in Cardiovascular Medicine, 2022)
Background and Objective: The association between sleep-related disorders and cardiovascular diseases (CVDs) remains controversial and lacks epidemiological evidence in the general population. We investigated whether sleep-related disorders are related to CVDs in a large, nationally representative, diverse sample of American adults. Methods: Data were collected from the National Health and Nutrition Examination Survey (NHANES) 2005-2008. Logistic regression was performed to explore associations of sleep-related disorders with the prevalence of total and specific CVDs. Stratified subgroup analysis was performed to exclude interactions between variables and sleep-related disorders. Nonlinearity was explored using restricted cubic splines. Results: In total, 7,850 participants aged over 20 years were included. After controlling for confounders, multivariate regression analysis showed that sleep problems were associated increases in risk of 75% for CVD, 128% for congestive heart failure, 44% for coronary heart disease, 96% for angina pectoris, 105% for heart attack and 78% for stroke. Daytime sleepiness was associated increases in risk of 54% for CVD, 73% for congestive heart failure, 53% for angina pectoris, 51% for heart attack, and 60% for stroke. Participants with insufficient sleep had a 1.42-fold higher likelihood of CVD and a 1.59-fold higher likelihood of heart attack than participants with adequate sleep. Prolonged sleep-onset latency was associated with an increased risk of CVD, congestive heart failure and heart attack. Short sleep-onset latency was associated with a 36% reduction in stroke risk. The association of sleep problems with CVD risk was more pronounced in the group younger than 60 years, and the relationship between short sleep-onset latency and total CVD differed by sex. Additionally, restricted cubic splines confirmed a linear relationship between sleep-onset latency time and CVD and a nonlinear relationship between sleep duration and CVD. Conclusion: According to a limited NHANES sample used to examine sleep-related disorders and CVD, total and specific CVDs could be associated with certain sleep-related disorders. Additionally, our study uniquely indicates that CVD risk should be considered in participants younger than 60 years with sleep problems, and shortened sleep-onset latency may be a CVD protective factor in females.